Expanded carrier screening: A current perspective. (November 2018) - Mastantuoni, Enrica; Saccone, Gabriele; Al-Kouatly, Huda B.; Paternoster, Mariano; D'Alessandro, Pietro; Arduino, Bruno; Carbone, Luigi; Esposito, Giuseppina; Raffone, Antonio; De Vivo, Valentino; Maruotti, Giuseppe Maria; Berghella, Vincenzo; et al.
Abstract: Prenatal carrier screening has expanded to include a large number of genes offered to all couples considering pregnancy or with an ongoing pregnancy. Expanded carrier screening refers to identification of carriers of single-gene disorders outside of traditional screening guidelines. Expanded carrier screening panels include numerous autosomal recessive and X-linked genetic conditions, including those with a very low carrier frequency, as well as those with mild or incompletely penetrant phenotype. Therefore, the clinical utility of these panels is still subject of debate. Priority should be given to carrier screening panels that include a comprehensive set of severe childhood-onset disorders. Psychosocial support and genetic couseling should be available prior to screening and for the return of positive results. Systems are needed to reduce the risk of misinterpreting results. Finally, attention should be paid on the impact of expanded carrier screening on health care organizations and burden of cost.